The assimilation and elimination of cesium by freshwater invertebrates - Tostowaryk, Tracy M., author; Whicker, F. Ward, advisor; Rowan, David, advisor; Clements, W. H. (William H.), committee member; Hinton, Tom, committee member (Colorado State University. Libraries, 2000)
Freshwater invertebrates are important vectors of radioactive cesium 134Cs and 137CS) in aquatic food webs, yet little is known about their cesium uptake and loss kinetics. This study provides a detailed investigation of cesium assimilation and elimination by freshwater invertebrates. Using five common freshwater invertebrates (Gammarus lacustris, Anisoptera sp. nymphs, Claassenia sabulosa and Megarcys signata nymphs, and Orconetes sp.), a variety of food types (oligochaete worms, mayfly nymphs and algae) and six temperature treatments (3.5 to 30°C), the following hypotheses were tested: 1) cesium elimination rates are a positive function of water temperature; 2) cesium elimination rates increase with decreasing body size; 3) assimilation efficiencies range between 0.6 and 0.8 for diet items low in clay. Cesium loss exhibited first order, non-linear kinetics, best described by a two component exponential model. Cesium assimilation efficiencies were higher for invertebrates fed oligochaetes (0.77) and algae (0.80) than those fed mayfly nymphs (0.20). Cesium elimination rate constants ranged from 0.002 to 0.125 d-1 across taxa and temperatures. Within each taxon, linear regressions of the natural logarithm of cesium elimination rate constants on temperature yielded positive, significant relationships. As temperature coefficients were not significantly different across taxa, the data were combined into a general model of cesium elimination by freshwater invertebrates as a function of temperature, body size and a categorical variable for thermal optima (warmwater and cool-water adapted taxa). Cesium elimination rate constants were found to increase with temperature, decrease with body size, and be much lower for warmwater adapted invertebrates than cool-water adapted invertebrates. Both the cesium assimilation efficiencies and general model of cesium elimination rate constants for freshwater invertebrates are in excellent agreement with those for fish. Quantification of cesium assimilation efficiencies and elimination rate constants for freshwater invertebrates allows, for the first time, development of dynamic aquatic food web models for .risk assessments, and it enables the in situ quantification of invertebrate feeding rates and other bioenergetic parameters.
Department Head: Daniel E. Binkley.